Readiness and Ability to Self-Development of Gifted Rural Schoolchildren - Olga G. Kholodkova; Galina L. Parfenova; Olga A. Bokova (National Research Mordova State University, 2022)
Introduction. The article examines the problem of the formation of readiness and ability for self-development among gifted rural schoolchildren as resource qualities of a personality that characterize the potential of its self-realization. The relevance of the problem is determined by the systematic nature of the support of gifted schoolchildren, which assumes consideration of the individual qualities of gifted subjects, the specifics of which, in this case, is determined by living in rural areas. One of the key tasks of systematic psychological and pedagogical support of gifted children and students in rural schools is to help them to know and understand themselves, to reveal their interests, abilities, to teach them to use the properties of their personality as internal resources for effective interaction in society, successful learning, self-realization and high achievements. Materials and Methods. The sample of subjects included 420 schoolchildren from eight rural schools of the Altai Territory. Among them, 49 people identified as gifted. The basic model for identifying the giftedness of schoolchildren was the three-factor model of J. Renzulli. To study the readiness for self-development, the ability to self-development and self-education, test methods and questionnaires were used. Results. It is empirically revealed that the majority of gifted rural schoolchildren has low readiness for self-development and has differences by gender: it is higher in boys than in girls. Among the schoolchildren with undiagnosed giftedness there are more of those who are ready for self-improvement, but not ready for self-knowledge. Intellectual characteristics are more pronounced in gifted boys than in gifted girls; creative characteristics are more pronounced in gifted girls than in gifted boys. Discussion and Conclusion. The results of the study open up new opportunities for the development of practical methods of psychological and pedagogical activity for the correction and prevention of the identified difficulties in the conditions of rural educational and cultural space. The materials of the article will be useful to the subjects of the educational space, engaged in system interaction in the effective development of the giftedness of children and youth.